DIGITAL SUFISM: THE TRANSFORMATION OF PIETY IN GUS ULIL'S ONLINE TEACHINGS - Hakim, Putri Rahmah Nur; Sampurno, Margo Teguh; Abdullah, Irwan; Kailani, Najib; Larasati, Yuniar Galuh (UIN Antasari Banjarmasin, 2024)
The transformation of da'wah from offline to online is an important issue that needs to be studied in the context of the development of digital technology and changing patterns of social interaction in the modern era. While some previous studies have discussed the impact of digitalisation on religious practice, there is a gap in understanding how social media platforms such as Facebook change the dynamics of da'wah, especially in the context of recitations led by scholars such as Gus Ulil. The focus of this study is to examine how the digitalisation of da'wah affects the spiritual interactions between ulama and their followers, and how these changes affect the meaning and experience of religiosity in the digital era. This study is qualitative in nature with a focus on online recitations on Facebook, where data was collected through participatory observation, content analysis, and in-depth interviews. The data analysis process was conducted through the stages of coding, categorisation, and interpretation to understand the patterns of interaction and the impact of online dakwah. The key findings of this study show that digitalisation not only expands the reach of da'wah, but also changes the structure of religious communities to become more private and exclusive. Recommendations from this study include the development of more inclusive policies to support the sustainability of digital da'wah, as well as methodological approaches that can be used to improve the sustainability of digital da'wah.